University learning: what it is and what is learned from the perspective of the students. Contributions from and for psychopedagogy - Petric, Natalia; Sucari, Wilson (Revista Innova Educación, 2020)
The article presents the results of an investigation about the meanings that university students give to the learning that occurs in this context. We worked with a qualitative design in order to discover and deepen the dimensions involved in this learning, the definitions about it and the strategies put into play. The sample consisted of twenty-five students of the last year of careers taught at the Paraná Headquarters of the Universidad Católica Argentina (UCA). The focused interview was used. It included the technique of choosing objects that allows the construction of metaphors, in this case of university learning. Thus, the findings allow the notion of university learning to be expanded to fields not directly linked to the academic, cognitive or performance aspects, but to issues that specify the curricular and didactic, subjective, family, relational and teaching dimensions. In addition, they describe the objects of learning (WHAT is learned), elucidate the definitions about it (WHAT it is) and determine strategies for studying and passing, ways of learning and advancing in the career respectively. The conclusions refer to positioning an inescapable psychopedagogical view that articulates different theoretical frameworks.
Keywords: Learning; psychopedagogy; university